2021
DOI: 10.1246/cl.210706
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Aromatic Ketones under Mild Conditions over Pd-loaded Hydrogen Molybdenum Bronze with Plasmonic Features

Abstract: Reduction of α-MoO3via “hydrogen spillover” process mediated by noble metal nanoparticles leads to a formation of hydrogen molybdenum bronze with plasmon-induced optical features. We herein report that Pd-loaded hydrogen molybdenum bronze effectively promotes the hydrodeoxygenation of aromatic ketones to the corresponding alkyl aromatics at room temperature and under atmospheric pressure of H2. The catalyst shows a further enhanced catalytic activity under the irradiation of visible light due to the plasmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The preceding results indicate that the intercalation of hydrogen ions into MoO 3 allows a significant number of free electrons to be stored in the Mo 4d orbital, enabling an LSPR effect in the visible region. 58 3. Application of a-MoO 3…”
Section: Plasmonic Effects Of Non-stoichiometric H X Moo 3àymentioning
confidence: 99%
“…The preceding results indicate that the intercalation of hydrogen ions into MoO 3 allows a significant number of free electrons to be stored in the Mo 4d orbital, enabling an LSPR effect in the visible region. 58 3. Application of a-MoO 3…”
Section: Plasmonic Effects Of Non-stoichiometric H X Moo 3àymentioning
confidence: 99%
“…Our group has demonstrated that efficient HDO of sulfoxides can be achieved under H 2 gas at 1 atm and room temperature by introducing oxygen defects on the surface of the Pt/H x MoO 3– y catalyst . Furthermore, we have reported that Pd/H x MoO 3– y also exhibits a unique catalytic activity in the HDO reaction of aromatic ketones under mild conditions owing to the Brønsted acidity of the abundant hydroxyl groups on the surface …”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, we have reported that Pd/H x MoO 3−y also exhibits a unique catalytic activity in the HDO reaction of aromatic ketones under mild conditions owing to the Brønsted acidity of the abundant hydroxyl groups on the surface. 26 Noteworthy, some reduced transition metal oxides exhibit surface plasmon resonance (SPR) effects, allowing them to absorb light from the visible to near-infrared (NIR) spectra (e.g., Bi 2 O 3−x , In 2 O 3−x , NiO x , and H x MoO 3−y ), 27−30 which can be attributed to the introduction of H atoms and oxygen defects in transition metal oxides, resulting in a high density of free charge carriers in the solid and thus endowing them SPR effects similar to those of metal nanoparticles (NPs) (such as Au, Ag, and Cu). 31 Among those, WO 3 is a well-known reducible metal oxide with a unique SPR effect when it forms hydrogen bronze (H x WO 3−y ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…These phenomena, and their underlying dynamics, involve an interaction between the hydrogen sub-lattice and the oxygen sub-lattice, which are fundamental to the understanding of the properties of the bronzes. Hydrogen mobility is key to the excellent performance of the Pddecorated bronzes as hydrogenation catalysts at ambient conditions [1,[5][6][7][8][9][10][11][12]. The efficient transport of hydrogen species through the bulk toward the catalyst surface enhances the catalytic performance of the bronze.…”
Section: Introductionmentioning
confidence: 99%